2011
DOI: 10.12927/hcpol.2011.22350
|View full text |Cite
|
Sign up to set email alerts
|

Are Primary Healthcare Organizational Attributes Associated with Patient Self-Efficacy for Managing Chronic Disease?

Abstract: Our objective was to explore how individual and primary healthcare (PHC) organizational attributes influence patients' ability in chronic illness self-management. We conducted a cohort study, recruiting 776 adults with chronic disease from 33 PHC settings in the province of quebec. Organizational data on the PHC clinics were obtained from a prior study. Participants were interviewed at baseline, 6 and 12 months, responding to questionnaires on self-efficacy, health status, socio-demographics, healthcare use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Few authors have reported on the magnitude of organizational contribution to quality of care. 7,[36][37][38] Our observations about practice size agree with previous reports. 6,11,16 The observed associations with visit duration and physician remuneration should, however, be viewed with caution.…”
Section: Discussionsupporting
confidence: 92%
“…Few authors have reported on the magnitude of organizational contribution to quality of care. 7,[36][37][38] Our observations about practice size agree with previous reports. 6,11,16 The observed associations with visit duration and physician remuneration should, however, be viewed with caution.…”
Section: Discussionsupporting
confidence: 92%
“…Since relevant and available competence is imperative to gain positive effects from implementation [ 42 ], discrepancies put strains especially on health care and its providers to bridge the gap. Our results were similar to studies on self-management support that emphasized inter-professional cooperation, [ 11 , 43 ] and strategies to improve user-involvement [ 44 ] as core skills for health professionals engaged in self-management support. In line with Liaw and colleagues [ 45 ], knowledge and skills in adjustments to cultural and social norms would be important to enhance in support programme development and running.…”
Section: Discussionsupporting
confidence: 87%
“…Within Canada, eight primary care organizational attribute data collection tools were identified (Table ). Seven of these tools collected primary care organizational attribute information at a jurisdictional level within the provinces of Alberta [42,43], Ontario [11–13,44–47], Québec [48–54] and Nova Scotia [55].…”
Section: Resultsmentioning
confidence: 99%